The role of candidate pharmacogenetic variants in determining valproic acid efficacy, toxicity and concentrations in patients with epilepsy - Yazbeck, Hady; Youssef, Joe; Nasreddine, Wassim; El Kurdi, Abdullah; Zgheib, Nathalie; Beydoun, Ahmad (Frontiers in Pharmacology, 2024)
Background: Antiseizure medications (ASM) exhibit considerable interindividual variability in terms of efficacy and adverse events. Genetic variation is thought to contribute to these differences in clinical outcomes. Specifically, the response to valproic acid (VPA), a widely used ASM, is influenced by multiple pharmacogenetic factors. However, and in contrast to other ASMs such as phenytoin and carbamazepine, there is a paucity of data on the association between VPA and various gene variants.The aim of this study was hence to evaluate the influence of candidate pharmacogenetic variants on VPA efficacy, toxicity and serum concentrations in a homogeneous cohort of patients newly diagnosed with genetic generalized epilepsies (GGE).In this prospective cohort study, demographic, clinical and treatment outcomes of GGE patients were retrieved from their medical records. Whole exome sequencing was performed in collaboration with Epi25. Gene variants associated with VPA efficacy, metabolism and toxicities were retrieved from PharmGKB. An analysis was then conducted to explore potential associations between these gene variants and VPA clinical outcomes.Of the 166 patients included, 60 (36.1%) experienced treatment failure while 106 (63.9%) achieved treatment success. After adjusting for VPA maintenance dose, carriers of the rs3892097 (CYP2D6) variant were 2.5 times more likely to experience treatment failure compared to wildtype (P = 0.026). The rs1057910 variant (CYP2C9*3) was associated with increased serum VPA concentrations (P = 0.034). Moreover, the rs1137101 variant (LEPR gene, a metabolism regulator) was significantly associated with a higher frequency of hair loss (P = 0.026), while the rs4480 variant (SOD2 gene, encoding for a mitochondrial scavenging enzyme) was correlated with a lower frequency of hair loss (P = 0.026). Finally, carriers of the rs1137101 variant (LEPR) were at a higher risk of weight gain (P = 0.015).These findings highlight the role of genetic factors in VPA treatment and underscore the potential for developing therapeutic strategies to enhance patient outcomes and minimize adverse effects.